(untitled) (Cadernos de Sociomuseologia, 2017)
The present text is a result of the dissertation presented in the Postgraduate Program in Museology of the Federal University of Bahia, entitled: The representation of black women in the museums of Salvador: a black and white analysis that deals with a study of a critical, About the place that is attributed to black women, in the long-term exhibitions, in the museums of historical typology in Salvador, Bahia, Brazil. The article proposes a reflection during the process of meaning of the objects of the collections that treat only the black women in the context of the slavery. In this process, the role of museum professionals and how they rank collections and subalternate subjects is discussed. There is an appropriation of my speaking place as a researcher and militant of the cause of the black woman, in the context of the construction of places of memories that deal with the trajectories and narratives of these women. The article brings the theoretical contribution of Freire (1989), to deal with the relations between man and the world; Hooks (2013) sustains the discussion of the place of the black intellectual in the academy; Menezes (1994) and Cury (2005), to deal with museological expositions, among other contributions. Keywords: black women, museums of Salvador, representation, Museology.